Creative Content Marketing In Scientific Publication Management In Industrial Era 4.0 - Rahardja, Untung; Lutfiani, Ninda; Amelia, Sindy (APTISI Transactions on Management (ATM), 2019)
Industry 4.0 is a development trend of intelligent industries where all use of sophisticated equipment and are influenced by technological factors that are developing at this time. The emergence of industry 4.0 affects all aspects of the field including the field of marketing. Marketing is a marketing technique or introducing a product to the public to attract a lot of people. The role of Creative Content is needed in the publication of scientific papers in Industry 4.0. Creative Content can facilitate writers to publish scientific work. Social media is a medium for media creative content in scientific publications. However, the management of online scientific publications or e-journals is still of little use. To achieve Creative Content in scientific publications the need to conduct research or research to find out and obtain information about the role of creative content in scientific publications. The method used in the research is literature study, design, and mind map. Doing research / research is not just going to a place but looking for data in a journal is also needed. This study aims to determine the importance of digital content to improve the dissemination of information on publication management or e-journal in its application within the scope of APTISI Transactions on Management (ATM) journals that have been published online. It can be concluded that the role of creative content in scientific publications is very important, especially in the face of the industrial era 4.0.